Understanding Two-Point Tangent-Curve Contact using JavaScript - Dhakal, Bed Prasad (Academic Journal of Mathematics Education, 2025)
This participatory action research (PAR) study investigated the design and implementation of JavaScript integrated Virtual Learning Environment (VLE) to enhance students’ conceptual understanding of "tangent-curve contact”. The study is conducted at Tribhuvan University in a course "Differential Geometry” during May–Sept 2024. The participants of this study were thirteen students, and the study followed four iterative cycles: 2D Javascript visualization of tangent contact, Javascript visualization of osculating circle, 3D JavaScript visualization, and Moodle based quiz as assessment. The study found that JavaScript visualization helped students in building a deeper understanding of the concept of tangent-curve contact. The findings highlight the pedagogical value of interactive visualizations within VLE and provide insights for technology integration in higher education, to implement evidence-based practices.